An investigation into teachers’ facilitation Of learners’ active learning in the classroom: A case study at a rural secondary school in bac ninh province = Nghiên cứu về cách thức giáo viên tạo điều kiện thuận lợi cho học sinh chủ động học trong lớp học: một nghiên cứu trường hợp ở một trường trung học cơ sở ở nông thôn trên địa bàn tỉnh Bắc Ninh - Nguyễn, Thi Thùy Linh (2020)
The main objective of this study was to explore teachers’ practices and challenges in implementing active learning in teaching English for secondary students. In conducting the study, the researcher employed qualitative approach. To collect the data for the study, two main research instruments were employed. They are: class-room observation and semi-structured interviews conducted with two teachers of English at the secondary school. Accordingly, the findings from classroom observation indicated that the teacher made an effort to facilitate her students to learn actively; however, there were some barriers that made her effort unsuccessful. In their best attempt to implement the strategy, the techniques those teachers of English frequently used were question-and-answer, think-pair-share, discussion and games to solve various problems. However, some motivational techniques that the observed teachers were employing in the class did not facilitate students’ active learning. The results from the interviews with those teachers, revealed that most teachers had the perception that active learning was one of the significant strategies which could help students to facilitate independent learning. Nevertheless, most teachers of English did not put it into practice fully due to various reasons. According to the researcher’s exploration, the difficulties that were identified as major constraints affecting the implementation of active learning for students at secondary schools were content covering, preparation before class, lack of materials and equipment, class size and student factors. Finally, implications and further studies were proposed.